The SDSS-IV in 2014: a demographic snapshot - Lundgren, Britt; Kinemuchi, Karen; Zasowski, Gail; Lucatello, Sara; Diamond-Stanic, Aleksandar M.; Tremonti, Christy A.; Myers, Adam D.; Aragón-Salamanca, Alfonso; Gillespie, Bruce; Ho, Shirley; Gallagher, John S. (IOP Publishing, 2015)
Many astronomers now participate in large international scientific collaborations, and it is important to examine whether these structures foster a healthy scientific climate that is inclusive and diverse. The Committee on the Participation of Women in the Sloan Digital Sky Survey (CPWS) was formed to evaluate the demographics and gender climate within SDSS-IV, one of the largest and most geographically distributed astronomical collaborations. In April 2014, the CPWS administered a voluntary demographic survey to establish a baseline for the incipient SDSS-IV, which began observations in July 2014. We received responses from 250 participants (46% of the active membership). Half of the survey respondents were located in the United States or Canada and 30% were based in Europe. Approximately 65% were faculty or research scientists and 31% were postdocs or graduate students. Eleven percent of survey respondents considered themselves to be an ethnic minority at their current institution. Twenty-five percent of the SDSS-IV collaboration members are women, a fraction that is consistent with the US astronomical community, but substantially higher than the fraction of women in the International Astronomical Union (16%). Approximately equal fractions of men and women report holding positions of leadership in the collaboration. When binned by academic age and career level, men and women also assume leadership roles at approximately equal rates, in a way that increases steadily for both genders with increasing seniority. In this sense, SDSS-IV has been successful in recruiting leaders that are representative of the collaboration. That said, it is clear that more progress needs to be made towards achieving gender balance and increasing diversity in the field of astronomy, and there is still room for improvement in the membership and leadership of SDSS-IV. For example, at the highest level of SDSS-IV leadership, women disproportionately assume roles related to education and public outreach. The goal of the CPWS is to use these initial data to establish a baseline for tracking demographics over time as we work to assess and improve the climate of SDSS-IV.